DAMPAK ONLINE PROMOTION MEMPENGARUHI PURCHASE INTENTION MELALUI INSTAGRAM ADVERTISING DARI PRODUK-PRODUK DI TOKOPEDIA - Sigumonrong, Ferliro; Budiono, Sidik (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Instagram Ads become one of the marketing media that oftenly used in giving information about online promotion towards the buyers target that connected with products that sold on the Tokopedia platform. This research has a total of 200 respondents which are using Instagram and Tokopedia as the research obhect with spreading method through online questionnaire. The research summary gives a conclusion to use Instagram Advertising as an online promotion platform which will increase the purchase intention of products in Tokopedia.